2013
DOI: 10.1186/1465-9921-14-131
|View full text |Cite
|
Sign up to set email alerts
|

Computer quantification of airway collapse on forced expiration to predict the presence of emphysema

Abstract: BackgroundSpirometric parameters are the mainstay for diagnosis of COPD, but cannot distinguish airway obstruction from emphysema. We aimed to develop a computer model that quantifies airway collapse on forced expiratory flow–volume loops. We then explored and validated the relationship of airway collapse with computed tomography (CT) diagnosed emphysema in two large independent cohorts.MethodsA computer model was developed in 513 Caucasian individuals with ≥15 pack-years who performed spirometry, diffusion ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…How this disturbance should be defined is still unclear, but it is obvious that we should be less restrictive than what the current ATS/ERS rules are suggesting. One challenging approach may be the inclusion of new more selective parameters of PFTs to improve the differentiation between these diseases [29,30] . Another problem for the development of automated interpretation of lung function is its inherent dependency on the prevalence of the diseases comprised in the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…How this disturbance should be defined is still unclear, but it is obvious that we should be less restrictive than what the current ATS/ERS rules are suggesting. One challenging approach may be the inclusion of new more selective parameters of PFTs to improve the differentiation between these diseases [29,30] . Another problem for the development of automated interpretation of lung function is its inherent dependency on the prevalence of the diseases comprised in the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…For low and medium grade emphysematous changes, HRCT is clearly superior to conventional X-ray imaging [18]. In addition to visual emphysema grading as described by Bankier et al [19], quantitative methods particularly demonstrate high correlation with pulmonary parameters [20]. These offer measurement during inspiration (extent of emphysema) as well as expiration (air trapping as correlate of the extent of air passage obstruction).…”
Section: Density Reduction Of Lung Parenchymamentioning
confidence: 99%
“…However, due to the loss of supporting structure and airway collapse during forced expiration, emphysema is featured by an abrupt decrease in flow following PEF and, thereafter, a more gradual decrease in flow, which results in a sharp angle in the MEFV curve 11–14. This angle in the MEFV curve was called the “angle of collapse (AC)” 12,14…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that a sharp AC in the MEFV curve was an indicator of emphysema 1214. In clinical practice, the shape of the MEFV curve is usually evaluated by visual assessment, as only a few studies have used computer quantification methods to evaluate the shape of this curve 12,14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation